Microbiological Evaluation of Raw Meat Products Available in Local Markets of Karachi, Pakistan: Microbial Evaluation of Raw Meat Products - Zafar, Ayesha; Ahmed, Erum; Wajiha, Hafiza; Khan, Abdul Basit (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2016)
Contaminated food products have been reported to be responsible for numerous food borne diseases all around the world. Microbial contaminants have been shown to be present in a wide variety of food products, especially in raw meat. For this reason, their isolation and detection in food is crucial for the safety of public health. The purpose of this research was to evaluate the microbiological quality of different meat samples including chicken, mutton and beef. Thirty (30) meat samples were purchased from different local meat retailer shops in Karachi. These samples were analyzed for their total aerobic count, total coliform count, fecal coliforms and Salmonellae according to standard methods. Examination of meat samples revealed that almost all samples were unfit for human consumption due to the presence of high aerobic count, coliforms, fecal coliforms and Salmonella spp. The average aerobic count log10cfu/g of chicken, mutton and beef samples was 6.67, 6.38 and 7.05 respectively. Out of 30 samples, 29 were heavily contaminated with coliforms and among them 26 were positive for fecal coliforms. The results also showed that 13 out of 30 meat samples were positive for Salmonella using conventional and PCR methods. The microbiological quality of meat was associated with handling and processing in unhygienic conditions. It was concluded that the food industry and regulatory authorities concerning food safety should take better control measures to improve food hygiene and prevent the contamination of food to maintain public health status and also control the rate of incidence of food borne diseases.